The effects of transformational leadership on followers’ perceived work characteristics and psychological well-being : a longitudinal study - Karina Nielsen; Raymond Randall; Joanna Yarker; Sten-Olof Brenner (2008)
There is some evidence that transformational leadership style is linked to employee well-being at work. However, it is not clear whether this is due to (i) a direct relationship between leadership behaviour and well-being outcomes, or (ii) a relationship between leadership behaviour and well-being that is mediated by followers’ perceived work characteristics. This paper examines the validity of these two mechanisms using data from a longitudinal questionnaire study of staff within the elderly care sector in a Danish local government. A theory-driven model of the relationships between leadership, work characteristics and well-being was tested using Structural Equation Modelling. The results indicated that followers’ perceptions of their work characteristics do mediate the relationship between transformational leadership style and well-being. However, there was only limited evidence of the existence of a direct path between leadership behaviour and employee well-being. These findings have important implications for design, implementation and management of efforts to improve employee well-being.